ibn 'arabi dan teori al-llah al-ma'bud - Iskandar Arnel (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2013)
Global Theology ideas, Transcendental Unity of God, and Religious Pluralism. Among Muslims, the most so that the impression arises that eminent architect Wahdah al-existent concept is included in all the similarities about God that should be worshiped. This study found that Ibn ‘ Arabi accept and follow the teachings of the Apostles and the Book.